CODEWORDS CORRECTION ON THE BASIS OF PARITY CHECKS - A. S. Poljakov; V. E. Samsonov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
To find errors in codewords the parity check on axis and diagonals (main and auxiliary) of code plain is proposed. The results of such checks are used in algorithm to find multiple errors in lines and columns of code plane.